The book of Shane - Eliopulos, Nick (Spirit animals., 2015)
"Shane is just a boy, but in order to free his people, he's resolved to do whatever--to become whomever--his mission requires. Throughout their journey to save the world, Conor, Abeke, Meilin, and Rollan have faced this dangerous foe again and again. But none have learned truth of the boy who nearly changed the course of history forever."--Publisher.